Effects of in ovo nutrition on broiler performance: a review (Research, Society and Development, 2021)
The productive efficiency obtained through broiler chicken' breeding promoted a greater need for embryonic nutritional supply. For this, the in ovo inoculation of solutions containing nutrients and exogenous substances has become an important technique to increase energy reserves and, consequently, obtain better performance of birds after hatching. Thus, our objective was to review both the methodologies and nutrients used at the in ovo nutrition. Furthermore, we focused on the effects of this technique on the broilers' production. Carbohydrates are used as one of the primary sources of energy for the post-hatch embryo, as they guarantee an increase in glucose availability. Proteins and amino acids are essential for the efficiency of protein deposition after hatching. Probiotics and prebiotics provide better gastrointestinal' development and integrity, and consequently, guarantee animals' intestinal health. Finally, the use of vitamins and minerals contributes to animals' immunity, skeletal development during the incubation and post-hatch periods, between several other functions. Given this, in ovo nutrition techniques might promote zootechnical efficiency of broiler chicken in the post-hatch period, contributing to better performance of the animals until slaughter.